UPAYA MENINGKATKAN PRESTASI BELAJAR DALAM MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA PESERTA DIDIK KELAS IV A SD N NGEBUNG BERAN KULONPROGO - Andina Puji Lestari; Mahilda Dea Komalasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Indonesian language teaching in elementary schools is essential for optimizing students' language skills and academic achievement. However, observations implemented in grade four A at Ngebung Beran Elementary School indicate that Indonesian language learning achievement is low, reinforced by low learning achievement far below the Minimum Competency (KKM). By using the Cooperative Integrated Reading and Composition (CIRC) learning model, this study aims to improve Indonesian language learning achievement. The Kemmis and McTaggart Classroom Action Research (CAR) model, applied in this study, is divided into two cycles: planning, action implementation, observation, and reflection. In the second semester of the 2024–2025 academic year, eighteen grade IV A students from Ngebung Beran Elementary School became the research subjects. A learning achievement evaluation test in the form of multiple-choice questions and essays was used to collect data, and the percentage of learning completion was analyzed descriptively by calculating the percentage of learning completion. The research findings show that learning achievement increased in each cycle. Learning completion only reached 38.9% in the pre-cycle phase. This figure increased to 50% in the first cycle and 77.7% in the second cycle, exceeding the established success indicator of 75%. Furthermore, there was a significant increase in both teacher and student participation. As a result, fourth-grade students at SDN Ngebung Beran demonstrated improved Indonesian language skills thanks to the implementation of the CIRC learning model.